Ant-Man [videorecording (Blu-Ray)] - Rudd, Paul; Rudd, Paul; Lilly, Evangeline, 1979-; Stoll, Corey, 1976-; Cannavale, Bobby; Peña, Michael, 1976-; T. I., 1980-; Harris, Wood, 1969-; Greer, Judy, 1975-; Dastmalchian, David; Douglas, Michael, 1944-; Beck, Christophe, 1972-; et al. (Buena Vista Home Entertainment, 2017)
Armed with the astonishing ability to shrink in scale but increase in strength, con-man Scott Lang must embrace his inner-hero and help his mentor, Dr. Hank Pym, protect the secret behind his spectacular Ant-Man suit from a new generation of towering threats. Against seemingly insurmountable obstacles, Pym and Lang must plan and pull off a heist that will save the world.